Histopathological Study of Parotid Gland Tumors - Panchal, Nital Vishnubhai (Annals of Pathology and Laboratory Medicine, 2020)
Background: Parotid tumors are a morphologically and clinically diverse group of neoplasms, which may present significant diagnostic and management challenges. There are no reliable criterias to differentiate clinically benign from malignant lesions, so morphological evaluation is necessary. Hence, present study is undertaken to study spectrum of various histomorphological features. To study prevalence, age, sex distribution, histomorphological aspects and to differentiate benign from malignant parotid tumors. Methods: A total of 60 specimens of Parotid tumors analyzed from January 2012 to December 2014 from department of pathology, B.J Medical College, Ahmedabad. Specimens were fixed in formalin and sections were taken, processed and embedded in paraffin. The paraffin blocks were cut, slides made and stained with hematoxylin and eosin and examined. The tumors were classified according to (WHO) histological typing. The collected data were analyzed statistically. Result: Prevalence of parotid tumors was 0.47 %. All the patients presented with mass. Most of benign neoplasms occurred in 3rd and 4th decade, while malignant neoplasms more common in 5th decade. Males were more commonly affected. Pleomorphic adenoma was the commonest benign tumor and Mucoepidermoid carcinoma was the commonest malignant tumor. Conclusion: Although rare, parotid tumors are of importance because they show striking range of morphologic diversity between different tumor types and sometimes within an individual tumor mass. So, accurate diagnosis is essential which can be accomplished by histopathological examination.